Gender and STEM: Understanding Segregation in Science, Technology, Engineering and Mathematics - Maria Charles (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This volume features thirteen original chapters on the causes and consequences of gender segregation in scientific, technical, engineering, and mathematics ("STEM") occupations and fields of study. Although women have made great strides in equalizing access to labor markets and higher education, many STEM fields-particularly in the physical sciences and engineering-remain strongholds of gender segregation in the United States and other reputably gender-progressive societies. Policymakers, business leaders and activists have launched countless initiatives to diversify access to lucrative, high status occupations and ameliorate labor shortages that diminish innovation and competitiveness. Contributors to this volume apply diverse theoretical lenses and methodological approaches to understand the individual, interactional, organizational, and cultural dynamics that drive this segregation in the United States. Results show that the gender composition of scientific and technical fields varies a great deal over time and across organizational contexts and socio-demographic groups defined by race, ethnicity, class, and sexuality. But despite this variability, STEM work and STEM workers are widely presumed to be naturally and inevitably masculine. Research presented here reveals how these stereotypes combine with cultural beliefs about natural and fundamental differences between men and women to produce gendered aspirations and reinforce inequalities in the US scientific and technical workforce.